MIMO-OFDM System Using Bit Error Rate LS & MSE Analysis in Pilot Based Channel Estimation - Kaur, Randeep; Kaur, Sarabjeet (International Journal of Computer Sciences and Engineering, 2020)
With the expanding data moving over the remote frameworks, the channel capacity is lessening on a fast rate. To empower high piece rate information move we need wide channel capacity. This can be actualized by utilizing Multiple Input-Multiple Output (MIMO) that is, executing various sending recieving wires and numerous accepting radio wires. Symmetrical Frequency Division Multiplexing (OFDM) when utilized with MIMO improves the nature of the sending data and limit of the communicating channel. In this examination, MIMO and OFDM are applied together so as to decrease Signal-to-Noise Ratio (SNR) and improve the blunders experienced. Here, different channel assessment methods are dissected and executed, for example, (LS) Least Squares and (MMSE) Minimum Mean Square Error for MIMO-OFDM System. The Bit Error Rate, Mean Square Error (MSE) execution attributes of channel are examined for Quadrature Amplitude Modulation (QAM) conspire over the Additive White Gaussian clamor (AWGN). The general presentation of the proposed strategy and existing procedure is estimated utilizing BER and MSE.